2011
DOI: 10.1007/s13369-010-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Ray Attenuation Coefficient of Microalloyed Stainless Steel

Abstract: Gamma ray attenuation coefficients of microalloyed steel have been investigated. For this purposes the linear attenuation coefficients of steel have been measured at the photon energy of 0.662, 1.173 and 1.332 MeV and the results were compared with the calculation at the photon energy of 1-10 5 MeV obtained using XCOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…In literature, the µ values of Pb were measured as 0.618 cm -1 [3] and 0.616 cm -1 [22] Co -ray source is slightly over 0.4 cm -1 and boriding treatment and Ni concentration increases µ. From these results, one concluded that the borided Fe-Ni binary alloys show an appropriate radiation shielding performance.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In literature, the µ values of Pb were measured as 0.618 cm -1 [3] and 0.616 cm -1 [22] Co -ray source is slightly over 0.4 cm -1 and boriding treatment and Ni concentration increases µ. From these results, one concluded that the borided Fe-Ni binary alloys show an appropriate radiation shielding performance.…”
Section: Resultsmentioning
confidence: 83%
“…On the other hand, in recent years, boron has been used as an alternative for radiation shielding, although heavy metals such as Pb have been used for this purpose [4,5,10,11]. In relation to this, it has been shown that the borided AISI 316L and microalloyed stainless steels, especially in the middle energy region, have radiation shielding properties that are similar to those of Pb, the standard shielding material [3,4]. In these studies, it was clearly seen that the radiation shielding properties of steels were improved with a boriding process.…”
Section: Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, investigating the radioactive behaviour and shielding properties of these materials against X-rays and gamma rays is important. Previous studies have examined the behaviour of the attenuation properties of different types of stainless materials at varying photon energies [7][8][9][10][11][12][13][14][15][16]. Low gamma-ray energies have been widely used in practical radiography and medical diagnoses, where the interaction of gamma rays depends on the photon energy and the composition of materials, that is, the atomic numbers of elements.…”
Section: Introductionmentioning
confidence: 99%
“…When the interaction increase, more scattered photons will be produced. Therefore the scattered intensity increases when the density of material increases [11]. A specific name is given to the thickness at which half the radiation is either absorbed or scattered and the other half passes through the material, this thickness is called the half thickness.…”
mentioning
confidence: 99%